Direct Sequencing of tRNA by 2D-HELS-AA MS Seq Reveals Its Different Isoforms and Dynamic Base Modifications - Zhang, Ning; Shi, Shundi; Wang, Xuanting; Ni, Wenhao; Yuan, Xiaohong; Duan, Jiachen; Jia, Tony Z.; Yoo, Barney; Ziegler, Ashley; Russo, James J.; Li, Wenjia; Zhang, Shenglong (ACS chemical biology, 2020)
Post-transcriptional modifications are intrinsic to RNA structure and function. However, methods to sequence RNA typically require a cDNA intermediate and are either not able to sequence these modifications or are tailored to sequence one specific nucleotide modification only. Interestingly, some of these modifications occur with <100% frequency at their particular sites, and site-specific quantification of their stoichiometries is another challenge. Here, we report a direct method for sequencing tRNA without cDNA by integrating a two-dimensional hydrophobic RNA end-labeling strategy with an anchor-based algorithm in mass spectrometry-based sequencing (2D-HELS-AA MS Seq). The entire tRNA was sequenced and the identity, location, and stoichiometry of all eleven different RNA modifications was determined, five of which were not 100% modified, including a 2'-O-methylated G (Gm) in the wobble anticodon position as well as an -dimethylguanosine (m G), a 7-methylguanosine (m G), a 1-methyladenosine (m A), and a wybutosine (Y), suggesting numerous post-transcriptional regulations in tRNA. Two truncated isoforms at the 3'-CCA tail of the tRNA (75 nt with a 3'-CC tail (80% abundance) and 74 nt with a 3'-C tail (3% abundance)) were identified in addition to the full-length 3'-CCA-tailed tRNA (76 nt, 17% abundance). We discovered a new isoform with A-G transitions/editing at the 44 and 45 positions in the tRNA variable loop, and discuss possible mechanisms related to the emergence and functions of the isoforms with these base transitions or editing. Our method revealed new isoforms, base modifications, and RNA editing as well as their stoichiometries in the tRNA that cannot be determined by current cDNA-based methods, opening new opportunities in the field of epitranscriptomics.